Spermicidal and Microbicidal Compounds: In Search of an Efficient Multipurpose Strategy - Baptista, M.; Tavares, R.; Ramalho-Santos, J. (Current Medicinal Chemistry, 2014)
The search for cheap, easy-to-use and effective spermicides and microbicides to help avoid unwanted pregnancies and the transmission of sexually transmitted diseases has been ongoing for many years. This review takes into account compounds designed to act both as microbicides and spermicides for multipurpose prevention, and focuses on the required methodological studies to evaluate their safety, especially cytotoxicity. A comprehensive literature review was conducted on the synthesis, development, advantages and disadvantages of vaginal multi-function compounds. The available data shows that after several setbacks, there is a current interest in the synthesis and in the activity of novel dualfunction substances.. The study of well-known compounds with distinctive mechanisms of action provides a solid starting point to explore the possible development of such strategies. However, a completely safe and efficient compound for commercialization has yet to be identified.
Keywords: spermicides